FENTANYL: THE CRIME ENTERPRISE - Requenes, J. Isabel García (Seven Editora, 2025)
Fentanyl is a powerful synthetic opioid (manufactured in laboratories), 50 times more potent than heroin and 100 times stronger than morphine. In Mexico, it is classified under the General Health Law as a narcotic whose medical use is legal and regulated and supervised by the Federal Commission for the Protection against Sanitary Risks (COFEPRIS). “Fentanyl is a chemical substance that began to be used for medical purposes, indeed as an anesthetic, replacing morphine. However, parallel to this use, an entire black market emerged to use it in the production of drugs sold on the streets of the United States, which has caused this public health crisis” (Ágreda, 2025). Initially, its use was restricted to cardiac surgeries, as it could assist both the required sedative effect and postoperative pain management. Currently, it is used in combination with anesthetics during surgeries or for very intense pain, such as in the terminal stages of cancer. After the original injectable medical formulation, several other forms were developed, including transdermal patches, tablets, sprays, and lozenges, with the aim of providing broader administration options. The Sinaloa Cartel (SC) was the first to identify the business potential represented by fentanyl, followed by the Jalisco New Generation Cartel (CJNG) and other criminal groups. “One kilogram of fentanyl earns the cartel approximately USD 200,000 in the United States” (Grant, 2024). The leading cause of death from overdoses involving synthetic opioids in the United States is fentanyl, triggering a severe public health crisis; according to the Centers for Disease Control and Prevention (CDC), from 2021 to 2023 overdose deaths exceeded 100,000 annually. The reduction in fentanyl overdose deaths is largely attributed to the use of naloxone, known as Narcan, which rapidly restores normal breathing in overdose cases; however, its effects last only 30 to 90 minutes and require immediate medical attention. In Mexico, naloxone is classified as a psychotropic medication and is highly controlled, intended mainly for hospital use and requiring a prescription. In the United States, organized crime groups based in Mexico control the fentanyl supply to the U.S. drug market, particularly the Sinaloa Cartel (SC) and the Jalisco New Generation Cartel (CJNG), and in several cases local and regional U.S. criminal groups have mixed fentanyl with heroin to maximize profitability. DOI: https://doi.org/10.56238/sevened2025.036-143